VALUED BASES OF POLITICAL ANALYSIS - Рубанов, В.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
Influence of world valued-view and anthropological factors on the expertly-analytical process of preparation, acceptance and realization of public political decisions and programs is examined. It is drawn conclusion about the necessity of overcoming of standard conception of structure of political science knowledge, and also understanding of role of balance of values in professional activity of political analyst and political expert as basic subjects of the applied political analysis.